High penetrance of a pan-canina type rDNA family in intersection Rosa hybrids suggests strong selection of bivalent chromosomes in the section Caninae - Crhak Khaitova, Lucie; Werlemark, Gun; Kovarikova, Alena; Nybom, Hilde; Kovarik, Ales (Cytogenetic and genome research, 2014)
All dogroses (Rosa sect. Caninae) are characterized by the peculiar canina meiosis in which genetic material is unevenly distributed between female and male gametes. The pan-canina rDNA family (termed beta) appears to be conserved in all dogroses analyzed so far. Here, we have studied rDNAs in experimental hybrids obtained from open pollination of F1 plants derived from 2 independent intersectional crosses between the pentaploid dogrose species (2n = 5x = 35) Rosa rubiginosa as female parent (producing 4x egg cells due to the unique asymmetrical canina meiosis) and the tetraploid (2n = 4x = 28) garden rose R. hybrida 'André Brichet' as male parent (producing 2x pollen after normal meiosis). We analyzed the structure of rDNA units by molecular methods [CAPS and extensive sequencing of internal transcribed spacers (ITS)] and determined the number of loci on chromosomes by FISH. FISH showed that R. rubiginosa and 'André Brichet' harbored 5 and 4 highly heteromorphic rDNA loci, respectively. In the second generation of hybrid lines, we observed a reduced number of loci (4 and 5 instead of the expected 6). In R. rubiginosa and 'André Brichet', 2-3 major ITS types were found which is consistent with a weak homogenization pressure maintaining high diversity of ITS types in this genus. In contrast to expectation (the null hypothesis of Mendelian inheritance of ITS families), we observed reduced ITS diversity in some individuals of the second generation which might derive from self-fertilization or from a backcross to R. rubiginosa. In these individuals, the pan-canina beta family appeared to be markedly enriched, while the paternal families were lost or diminished in copies. Although the mechanism of biased meiotic transmission of certain rDNA types is currently unknown, we speculate that the bivalent-forming chromosomes carrying the beta rDNA family exhibit extraordinary pairing efficiency and/or are subjected to strong selection in Caninae polyploids.
Keywords: penetrance; chromozomy rostlin; klonování DNA; Penetrance; Polyploidy; genom rostlinný; Chromosomes, Plant; Pollen; pyl; Genome, Plant; DNA, Plant; DNA, Ribosomal; DNA rostlinná; ribozomální DNA; polyploidie; Cloning, Molecular; Rosa